2022
DOI: 10.1186/s13073-022-01069-z
|View full text |Cite
|
Sign up to set email alerts
|

Reanalysis of exome negative patients with rare disease: a pragmatic workflow for diagnostic applications

Abstract: Background Approximately two third of patients with a rare genetic disease remain undiagnosed after exome sequencing (ES). As part of our post-test counseling procedures, patients without a conclusive diagnosis are advised to recontact their referring clinician to discuss new diagnostic opportunities in due time. We performed a systematic study of genetically undiagnosed patients 5 years after their initial negative ES report to determine the efficiency of diverse reanalysis strategies. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 49 publications
(76 reference statements)
1
14
0
Order By: Relevance
“…For example, we previously showed that the probability of a negative srGS dataset harboring a clinically relevant variant increased from 1% within one year of a previous analysis to ~22% if more than three years have passed since a previous analysis (Hiatt et al 2018). Several other studies found similar results, with many reanalysis findings being due to recent publications of new gene-disease associations (Liu et al 2019;Schobers et al 2022;Hartley et al 2023).…”
Section: Discussionmentioning
confidence: 77%
See 2 more Smart Citations
“…For example, we previously showed that the probability of a negative srGS dataset harboring a clinically relevant variant increased from 1% within one year of a previous analysis to ~22% if more than three years have passed since a previous analysis (Hiatt et al 2018). Several other studies found similar results, with many reanalysis findings being due to recent publications of new gene-disease associations (Liu et al 2019;Schobers et al 2022;Hartley et al 2023).…”
Section: Discussionmentioning
confidence: 77%
“…In addition to changes in sequencing technology, the scope of knowledge about genes and our ability to annotate genetic variants has steadily increased. As such, systematic reanalysis of GS/ES data also leads to the discovery of previously overlooked clinically relevant variants, with diagnostic yield increases ranging from 4-31% depending on a variety of factors, most notably time since the previous analysis (Hiatt et al 2018; Liu et al 2019; Schobers et al 2022; Hartley et al 2023). While a variety of factors contribute to reanalysis discoveries, they often result from the discovery of new disease genes, which contributes to 42-75% of reanalysis findings (Hiatt et al 2018; Liu et al 2019; Schobers et al 2022; Hartley et al 2023).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This study evaluates the relationship between CGVs and their perceived roles in disease causation over time. There are some existing studies on nondiagnostic exome or genome reanalysis that have solved a portion of undiagnosed cases in addition to identifying CGVs (Eldomery et al, 2017;Hagman et al, 2017;Liu et al, 2019;Schobers et al, 2022;Shashi et al, 2019). However, few articles have discussed the follow-up of these CGVs and how many are ultimately determined to be diseasecausing over a period of time.…”
Section: Discussionmentioning
confidence: 99%
“…Following identification of the candidate gene, seven international genomic databases with over 120,000 exomes or genomes were interrogated for biallelic variants in DRD1 . These included three large databases of individuals with a range of rare diseases (Deciphering Developmental Disorders study [ 16 ]; NIH Undiagnosed Diseases Program [ 17 ]; Genomics England 100,000 Genomes Project [ 18 ]) and three databases of patients with undiagnosed neurological disorders (Radboud University Medical Centre Nijmegen [ 19 ]; the Institut für Humangenetik, Munich [ 20 ] and the Istituto Neurologico “Carlo Besta”, Milan [ 10 ]).…”
Section: Methodsmentioning
confidence: 99%